Strategy Open Unemployment Rate, Minimum Wage, and Social Spending: Determinants of Poverty in Sampang, Bangkalan, Sumenep, and Probolinggo - Pramudita Febrihana; Sishadiyati Sishadiyati (Cita konsultindo, 2024)
In 2023, the poverty rate in East Java Province is relatively high, reaching 10.35 percent, making it in third position as the poorest area on the island of Java. The highest contributors to poverty in this province consist of Sampang Regency, Bangkalan Regency, Sumenep Regency, and Probolinggo Regency. The high poverty rate makes the problem of poverty one of the priorities in every development. Therefore, it is necessary to measure the factors that affect poverty such as in the study using the variables of the Open Unemployment Rate, Minimum Wage, and the amount of government expenditure in providing social assistance. This study is a quantitative research using secondary data obtained from the Central Statistics Agency (BPS). In the analysis, linear regression of panel data using Eviews 10 and Fixed Effect Model (FEM) was used as the best model chosen. Based on the tests that have been carried out, using a significance level of 5%, it was found that the variable of the Open Unemployment Rate did not have a significant effect on the positive correlation with the Poverty Level. The Minimum Wage variable has a significant effect with a negative correlation with the Poverty Level. And the variable of Social Assistance Expenditure has a significant effect with a positive correlation with the Poverty Level.